2021
DOI: 10.1186/s12544-021-00472-8
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods analysis of mobility behavior changes in the COVID-19 era in a rural case study

Abstract: Background As a reaction to the novel coronavirus disease (COVID-19), countries around the globe have implemented various measures to reduce the spread of the virus. The transportation sector is particularly affected by the pandemic situation. The current study aims to contribute to the empirical knowledge regarding the effects of the coronavirus situation on the mobility of people by (1) broadening the perspective to the mobility rural area’s residents and (2) providing subjective data concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 41 publications
(51 reference statements)
2
27
0
Order By: Relevance
“…During the lockdown period in Spain, mobility to workplace dropped by 80%, compared to pre-COVID-19 trends [5]. The changes, however, less apparent in rural areas [4,17] and also can be seasonal, in particular, due to the start and stop of school season [2]. In Germany, Kolarova et al [16] found that travellers during the lockdown period switched to unimodal travel mode, e.g.…”
Section: Lesson 1: Mobility Impacts Of Covid Restrictions Vary Greatly Across Countries Geographic Areas and Demographic Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the lockdown period in Spain, mobility to workplace dropped by 80%, compared to pre-COVID-19 trends [5]. The changes, however, less apparent in rural areas [4,17] and also can be seasonal, in particular, due to the start and stop of school season [2]. In Germany, Kolarova et al [16] found that travellers during the lockdown period switched to unimodal travel mode, e.g.…”
Section: Lesson 1: Mobility Impacts Of Covid Restrictions Vary Greatly Across Countries Geographic Areas and Demographic Groupsmentioning
confidence: 99%
“…Furthermore the impacts of the measurements towards Covid19 are also different across household members. Male, in particular the ones of productive ages (40-60 s) and/or employed are the ones who still are likely to travel, 30-40% more than others, whilst elderly and women are the ones who have been reducing their travel to a greater extent [8,17]. The reasons why women are more negatively impacted by COVID-19 restrictions may not only be because they are taking a greater responsibility for the inner household chores, such as taking care of children when schools are forced to close, but also that the type of industries that has a high share of female workers, e.g.…”
Section: Lesson 1: Mobility Impacts Of Covid Restrictions Vary Greatly Across Countries Geographic Areas and Demographic Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mixed-methods design that combined both quantitative and qualitative methods (König & Dreßler 2021) was used for this study. This approach connects and embeds the data and is generally regarded as a more comprehensive way of integrating all aspects of a programme of inquiry (Tashakkori & Creswell 2007).…”
Section: Research Design and Samplingmentioning
confidence: 99%